A parametric study into the new design of a steel energy-absorbing connection. (15th August 2017) - Deihim, Mehdi; Kafi, Mohammad Ali
Highlights: An improved model for two half-ring connections as an energy absorber is proposed. A nonlinear FE model is presented and verified with previous experimental results. Employing supplementary plates will increase the strength and energy dissipation. Improvement by increasing thickness and overlap is limited to a certain level. Abstract: Several studies have investigated the ways of increasing the ductility of braced frames. A full ring comprised of steel half-ring plates as a novel energy-absorbing connection is among the ways that have been proposed to increase ductility. Experimental tests conducted in Semnan University have shown that besides high energy dissipation and high ductility, this element enjoys diversity in construction, ease of installment and replacement. Therefore, it can provide an appropriate substitute for damper rings. Low strength is the main shortcoming of this element which can be compensated by welding. But as the slit is welded, this contradicts the ductility of the rings. Based on finite element (FE), this study proposes an innovative improved model of half-ring connections through employing two supplementary steel plates so that welding is no longer required at the slit of the half-rings and strength would increase as a result. First, a nonlinear FE model for ring and two half-rings were proposed and then they were verified through experimental tests. Then, using this model, an improved FE model was proposed and nonlinear cyclic analyses were undertaken on it and on previous models in order to compare its global response and yielding performance with those of ring and half-ring models. In the next step, a set of parametric studies was performed in which the result of thickness and overlap variation on the hysteresis behavior of the new model was investigated. The results conveyed that using supplementary plates increased strength and energy dissipation in the new model compared to ring and half-ring models. These plates with a length of overlap improve ductility and their connection zone with half-ring plates is placed in an elastic zone. Parametric studies showed that variation in the thickness and overlap of supplementary plates greatly influenced the strength, ductility and the yielding effect of the half-rings. As the thickness and overlap increase, strength also increases, but this increase is limited to a certain level of strength. Thus, there is a significant relationship between the variation in thickness as well as the overlap length with the yielding effect in the connection zone of the supplementary plates with the half-ring, and some values are not recommended to be employed in thickness and overlap.